Automated system of shot blasting processing of free surfaces of metal products - Goryk, О.; Brykun, O.; Ivanov, O.; Koval’chuk, S.; Muravlov, V. (Scientific Progress & Innovations, 2023)
In mechanical engineering, there is a steady trend of manufacturing large-sized metal products from carbon steels with protective corrosion-resistant non-metallic coatings on surfaces in contact with aggressive environments. This allows you to abandon the use of expensive nickel-chromium-molybdenum steels and special alloys such as hastelloy, remanite, and others. At the same time, the process of blast-jet preparation of working surfaces for applying such coatings plays a major technological role, as it ensures the strength of the adhesion of the protective coating to the metal base of the product. A robotic system for shot blasting of free surfaces of products is proposed, consisting of a mobile robotic module, a precision electronic tool for scanning the processing surface and a central microcontrol module for controlling the complex. An improved shot blasting cleaning technology is presented with full integration of the technical characteristics of the created automated system and mutually agreed set and consequent parameters of shot blasting. The system allows remote processing of metal surfaces of free volumetric and spatial forms (missile hulls, aircraft fuselages, tanks for storing toxic liquids, torpedo hulls, hulls of chemical, biological, food, medical and other storage devices, hulls of ships and submarines) in compliance with high productivity, processing quality, minimization of energy and economic indicators and environmental safety. The practical value of the development is revealed in the production of capacitive products that are operated in special conditions and require reliable protection from the destructive aggressive effects of chemically active environments, high pressures and temperatures. The proposed technical-technological solutions can be used in the defense and civil-industrial sectors as a high-tech and economically justified alternative to other cleaning methods and common time-consuming manual labor for the preparation and corrosion protection of metal surfaces of products. The proposed automated shot blasting cleaning system will provide the following main advantages: improvement of the quality of processing of free surfaces of metal products; the possibility of online monitoring by a central microcontroller device according to the state of the processed surface; energy saving; ecological safety; versatility; minimization of the influence of the human factor on the process; reduction of technological time for product processing.